2019
DOI: 10.3892/ol.2019.10919
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Sonic Hedgehog pathway components in clear cell renal cell carcinoma

Abstract: Clear cell renal cell carcinoma (ccRCC) is the most common and the most aggressive histopathological subtype of kidney cancer, with patients exhibiting high mortality rates for metastatic tumors. The Sonic Hedgehog (SHH) pathway serves a crucial role in embryonic development. The abnormal activity of SHH signaling is observed in a broad range of malignancies. However, its role in ccRCC is still undetermined. The aim of the present study was to assess the expression of the SHH pathway genes in ccRCC. Neoplastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 39 publications
8
18
0
Order By: Relevance
“…One paper detected the immunohistochemical expression of PTCH1 in 140 ccRCC specimens and found that PTCH1 is more highly expressed in G3/G4 than in G1/G2 tumors (1.5-fold, p = 0.02) 50 , which was consistent with our findings of circPTCH1. Another study evaluated the expression of PTCH1 in 37 ccRCC tumor and control tissues, however, no statistically significant differences were observed 51 . Though circRNAs are typically described as having a similar function as their linear counterparts, antagonistic and independent functions of linear and circular RNA have also been reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…One paper detected the immunohistochemical expression of PTCH1 in 140 ccRCC specimens and found that PTCH1 is more highly expressed in G3/G4 than in G1/G2 tumors (1.5-fold, p = 0.02) 50 , which was consistent with our findings of circPTCH1. Another study evaluated the expression of PTCH1 in 37 ccRCC tumor and control tissues, however, no statistically significant differences were observed 51 . Though circRNAs are typically described as having a similar function as their linear counterparts, antagonistic and independent functions of linear and circular RNA have also been reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study by the authors ( 143 ), the expression of SHH pathway components in 37 ccRCC tissue samples, a significant correlation was identified among the expression of almost all SHH signaling genes at the mRNA level. Although the mRNA level of SHH , SMO and GLI1 was increased in ccRCC samples, compared to the morphologically unaltered kidney tissues, no association was observed between the expression rates of genes and the pathological features of patients.…”
Section: Sonic Hedgehog Signaling In Cancers Of the Urinary Tractmentioning
confidence: 81%
“…Since several studies have reported a SHH gene upregulation in RCC ( 140 , 142 , 143 ), the present review focused on the occurrence of the upstream protein and miRNA regulators of SHH expression in RCC. Shang et al ( 144 ) analyzed the mRNA expression rates of the ZIC2 gene in 533 ccRCC and 72 normal kidney samples (TCGA database), and found that the overexpression of ZIC2 mRNA was associated with age, TNM, histological grade and a shorter overall survival; thus, this gene can therefore be used as an independent prognostic factor in ccRCC.…”
Section: Sonic Hedgehog Signaling In Cancers Of the Urinary Tractmentioning
confidence: 99%
See 1 more Smart Citation
“…In early embryonic development, GLI members play a major role in the central nervous system; however, it is also involved in carcinogenesis and metastatic cascade niche ( Niewiadomski et al, 2019 ). Since amplified GLI was first observed in glioblastoma, it has now been commonly detected in the breast ( Song et al, 2016 ), lung ( Panneerselvam et al, 2019 ), pancreatic ( Kowolik et al, 2019 ), colorectal ( Park et al, 2019 ), leukemia ( Jetten, 2019 ), and renal cell carcinoma ( Kotulak-Chrzaszcz et al, 2019 ). It was also stated that high-expression GLI prevails tumor suppression mediated by p53 ( Abe et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%